Complementary Post-Preeclampsia Care Training for Midwives - Rini, Susilo; Rahmawati, Arni Nur (WASATHON Jurnal Pengabdian Masyarakat, 2024)
The cause of the highest maternal mortality rate in 2022 in Banyumas Regency is preeclampsia during the postpartum period. Symptoms of preeclampsia can occur in pregnant, parturient and postpartum women, namely hypertension, edema and proteinuria which appear at 20 weeks of pregnancy until the end of the first week after giving birth. This condition can cause severe morbidity, chronic disabilities and even death in mothers and babies without being detected previously. Even though the postpartum period is a critical period where the incidence of preeclampsia in pregnancy can continue into the postpartum period, early detection of preeclampsia is only carried out if there are signs of symptoms or complaints from the postpartum mother. This provides an opportunity for undetected cases of preeclampsia during the postpartum period. Therefore, there is a need for prevention efforts without having to wait for signs of preeclampsia to appear through the implementation of complementary postpartum care by midwives to prevent cases of preeclampsia in postpartum mothers. Target output of scientific journals and IPR publications.